1977
DOI: 10.1093/cvr/11.6.554
|View full text |Cite
|
Sign up to set email alerts
|

Collagen in the normal and hypertrophied human ventricle

Abstract: Estimates of the collagen concentration in human ventricles have been made from measurements of the hydroxyproline concentration. In the normal heart the concentration of collagen was higher in the right ventricle than in the left ventricle. Age had no effect on the ventricular concentration of collagen. Hypertrophy in the absence of a valvar lesion was not associated with an increased concentration of collagen but, owing to the increased size of the ventricle, there was an increase in the estimated total mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
1

Year Published

1980
1980
2004
2004

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(24 citation statements)
references
References 0 publications
3
20
1
Order By: Relevance
“…33 Kunkel et al,5 however, found substantially higher levels of volume fraction of collagen in COCM than we have by applying a trichrome (Table 12) and also a few investigations of biopsy material (M Hiroe, unpublished data) a distinct difference in diameter was found between muscle fibres from the right and left ventricle. Ontogenetically the cells of the two ventricles are identical, and the anatomical borders remain largely undefined in the adult heart; understanding of this "physiological hypertrophy" is thought to be essential for the comprehension of "pathological hypertrophy".…”
Section: Discussioncontrasting
confidence: 47%
“…33 Kunkel et al,5 however, found substantially higher levels of volume fraction of collagen in COCM than we have by applying a trichrome (Table 12) and also a few investigations of biopsy material (M Hiroe, unpublished data) a distinct difference in diameter was found between muscle fibres from the right and left ventricle. Ontogenetically the cells of the two ventricles are identical, and the anatomical borders remain largely undefined in the adult heart; understanding of this "physiological hypertrophy" is thought to be essential for the comprehension of "pathological hypertrophy".…”
Section: Discussioncontrasting
confidence: 47%
“…An impressive increment in the volume (or concentration) of myocardium occupied by collagen (see Figure 2) has been seen in adults with aortic valvular stenosis (Anderson et al, 1979;Caspari et al, 1977;Hess et al, 1981;Oldershaw et al, 1980;Schaper & Schaper, 1983;Schwarz et al, 1978;St John Sutton et al, 1980), children with congenital aortic stenosis or coarctation of the aorta (Cheitlin et al, 1980), and adults with systemic hypertension (Pearlman et al, 1982;Tanaka et al, 1986). In each circumstance, the accumulation of collagen, or myocardial fibrosis, was not associated with epicardial coronary artery disease.…”
Section: Remodelling Of the Collagen Matrixmentioning
confidence: 97%
“…20 Hydroxyproline values were then converted to collagen content by multiplying by a factor of 7.46. 21 …”
Section: Determination Of Collagen Contentmentioning
confidence: 99%